Preventing mobbing of nurses: a scoping review - Václavíková, Klára; Šoukalová, Kristýna; Kopecký, Michal; Molnárová, Lucia (My University, 2023)
Aim: The aim of this study was to search for and describe current scientific knowledge about preventive measures and programs used to prevent mobbing in the workplace. Design: A scoping review. Methods: In February 2022, searches were performed in selected licensed and free databases (EBSCOhost, Ovid Nursing, Scopus, and Taylor & Francis) based on keywords according to a PCC question using Boolean operators. Results: A total of 573 sources were found, of which 23 were subjected to critical analysis. Nine sources were included in the final review. The majority of studies confirmed the effectiveness of prevention programs aimed at teaching assertive communication and promoting teamwork and a positive work climate. Also highlighted was the need to increase nurses’ awareness and knowledge of mobbing issues. Conclusion: Mobbing is a society-wide phenomenon that significantly affects individuals and organizations. Preventive measures have an indispensable role in the effort to reduce the incidence of mobbing in nurses. Prevention programs, a positive organizational climate, and minimal tolerance of mobbing by the employer have been identified as highly effective measures. Increased awareness, assertive communication training and knowledge of procedures for reporting mobbing reduce the incidence of mobbing at the individual level.
Prevence mobbingu sester: scoping review
Keywords: mobbing; nurses; prevention; scoping review; mobbing; sestry; prevence; scoping review